2008
DOI: 10.1152/ajpregu.00797.2007
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dynamics of cardiac output, systemic O2 delivery, and lung O2 uptake at exercise onset in men in acute normobaric hypoxia

Abstract: We tested the hypothesis that vagal withdrawal plays a role in the rapid (phase I) cardiopulmonary response to exercise. To this aim, in five men (24.6 Ϯ 3.4 yr, 82.1 Ϯ 13.7 kg, maximal aerobic power 330 Ϯ 67 W), we determined beat-by-beat cardiac output (Q ), oxygen delivery (Q a O 2 ), and breathby-breath lung oxygen uptake (V O2) at light exercise (50 and 100 W) in normoxia and acute hypoxia (fraction of inspired O 2 ϭ 0.11), because the latter reduces resting vagal activity. We computed Q from stroke volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 58 publications
6
36
0
Order By: Relevance
“…2) lends further credence to earlier studies investigating the haemodynamic response to rest-to-exercise transitions. In these studies, it was shown that a steady state for cardiac output is attained between 30 (Lador et al 2006(Lador et al , 2008 and 60 s (De Cort et al 1991). Also, Davies et al (1972) found a rapid adjustment of cardiac output after increasing power (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2) lends further credence to earlier studies investigating the haemodynamic response to rest-to-exercise transitions. In these studies, it was shown that a steady state for cardiac output is attained between 30 (Lador et al 2006(Lador et al , 2008 and 60 s (De Cort et al 1991). Also, Davies et al (1972) found a rapid adjustment of cardiac output after increasing power (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence for quick adjustments of cardiac output to increased power comes from the examination of haemodynamics during rest-to-exercise transitions in healthy participants by determining cardiac function on a beat-by-beat basis, using Doppler ultrasound (De Cort et al 1991) or the model flow method (Lador et al 2006(Lador et al , 2008. These studies showed that when increasing power from rest to 50, 80, or 100 W (i.e., "rest-to-exercise" transitions), a steady state for cardiac output is quickly reached (e.g., within the first minute).…”
Section: Introductionmentioning
confidence: 99%
“…This being the case, the _ Q increase at exercise onset would be due only to the increase in f H . Yet a rapid increase in Q s was also demonstrated (Faisal et al 2009;Lador et al 2006Lador et al , 2008, clearly opening the way to a possible role for the Frank-Starling mechanism in the Q s increase at exercise start, likely activated by the sudden blood displacement from lower limbs to the heart due to muscle pump action. If this is so, then _ Q would be under dual control, neural (f H increase via vagal withdrawal) and mechanical (Q s increase via Frank-Starling mechanism).…”
Section: Kinetics Of Cardiac Output and Oxygen Delivery At Exercise Omentioning
confidence: 91%
“…Vagal blockade with atropine is known to suppress in fact the rapid component of the f H increase (Fagraeus and Linnarsson 1976). Coherently in hypoxia, when vagal activity is already reduced at rest, the amplitude of the f H increase in phase I is smaller than in normoxia (Lador et al 2008).…”
Section: Kinetics Of Cardiac Output and Oxygen Delivery At Exercise Omentioning
confidence: 99%
See 1 more Smart Citation